Ultimate capacity of reinforced concrete castellated beams subjected to external pre-stressing. (1st January 2022) - Nabil, Abdelaziz; Afefy, Hamdy M.; Kassem, Nesreen M.
Highlights: The most efficient reinforcement configuration for RC castellated beams is outlined. The behavior of RC castellated beams having large castellation is investigated experimentally. The effect of external pre-stressing is studied experimentally. Effects of castellation size and web post length are investigated numerically. Empirical expression for the ultimate capacity of RC castellated beams is proposed and verified against numerical results. Abstract: Introducing web openings in reinforced concrete (RC) beams became a common practice in order to provide easy passage ways for facility services. These openings can take any shape; however the most popular shapes are the square, the rectangular and the circular ones. In spite that the hexagonal shape (castellated) is normally used in steel beams, it is rarely used in reinforced concrete beams. Owing to the good appearance of the hexagonal shape, the flexural behavior of RC beams having multi-hexagonal openings (castellated beams) has been investigated. First, the most efficient reinforcement configuration of the castellated beams was chosen based on numerical sensitivity analysis. Then, the overall flexural performance of both monolithic and pre-stressed concrete castellated beams has been studied experimentally. Finally, a parametric study on the castellation size and web-post length has been carried out numerically in order to obtain a rational expression for estimating the ultimate capacity of castellated beams taking into account the controlling parameters. The numerical simulation of castellated beams provided the best internal reinforcement configuration from the viewpoint of both the ultimate capacity and the developed ductility. Besides, the experimental findings showed that providing castellated opening reduced the ultimate capacity, however, this reduction could be compensated by the application of external pre-stressing. Finally, an empirical expression was proposed in order to estimate the ultimate capacity of castellated beams subjected to external pre-stressing and their results showed good agreement with the numerical findings.